2011
DOI: 10.1051/0004-6361/201117665
|View full text |Cite
|
Sign up to set email alerts
|

Study of the many fluorescent lines and the absorption variability in GX 301−2 withXMM-Newton

Abstract: We present an in-depth study of the high mass X-ray binary (HMXB) GX 301−2 during its pre-periastron flare using data from the XMM-Newton satellite. The energy spectrum shows a power law continuum absorbed by a large equivalent hydrogen column on the order of 10 24 cm −2 and a prominent Fe Kα fluorescent emission line. Besides the Fe Kα line, evidence for Fe Kβ, Ni Kα, Ni Kβ, S Kα, Ar Kα, Ca Kα, and Cr Kα fluorescent lines is found. The observed line strengths are consistent with fluorescence in a cold absorbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 54 publications
(105 reference statements)
8
48
2
Order By: Relevance
“…Within these winds, dense structures with column densities on the order of 10 24 cm −2 can be reached, as seen in many other sources (e.g., GX 301−2 or IGR J16318−4848; Fürst et al 2011b;Barragán et al 2009). The absorption column of the partial coverer in 4U 1909+07 is measured to be also of that order, with values between (0.5-1) × 10 24 cm −2 , as seen in Tables 1-3.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Within these winds, dense structures with column densities on the order of 10 24 cm −2 can be reached, as seen in many other sources (e.g., GX 301−2 or IGR J16318−4848; Fürst et al 2011b;Barragán et al 2009). The absorption column of the partial coverer in 4U 1909+07 is measured to be also of that order, with values between (0.5-1) × 10 24 cm −2 , as seen in Tables 1-3.…”
Section: Discussionmentioning
confidence: 68%
“…A partial coverer can be used as an approximation to a complex structured stellar wind ("clumpy" wind), as seen in many HMXBs as well as isolated O and B stars (see, e.g., Oskinova et al 2007;Fürst et al 2011b, among many others). Within these winds, dense structures with column densities on the order of 10 24 cm −2 can be reached, as seen in many other sources (e.g., GX 301−2 or IGR J16318−4848; Fürst et al 2011b;Barragán et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of eclipse constrains the inclination angle in the range (44 • − 78 • ). A deep and variable 60 R. Walter et al cyclotron resonance feature is observed at hard X-rays Filippova et al, 2005;Fürst et al, 2011b). Spin up episodes have been observed and explained by the formation of transient accretion disks .…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be possible for an elliptical orbit to result in more moderate accretion rate variations via changes in the degree of Roche-lobe overflow as the distance between the compact object and its stellar companion varies (e.g., Church et al 2009). Alternatively, if NGC 5907 ULX1 is a wind-fed X-ray binary, the accretor could enter a higher-density region of the stellar wind, resulting in an enhanced accretion rate, similar to the case of GX 301−2 (Fürst et al 2011). However, sustaining the extreme luminosities observed from NGC 5907 ULX1 would be a major challenge for a wind-fed scenario.…”
Section: Discussionmentioning
confidence: 99%